Effects of inclusion levels of Indigofera sp. on feed intake, digestibility and body weight gain in kids fed Brachiaria ruziziensis. - Tarigan, Andi; Ginting, S. P. (Indonesian Animal Sciences Society, 2011)
Twenty weaned male goats (F1 of Boer x Kacang) with initial weight of 9 to 12 kg and ages ranging between 3.0 and 4.0 months were used in a study to evaluate the increasing inclusion of Indigofera sp foliage as a source of protein in diets based on chopped Brachiaria ruziziensis for growing goats. Five goats were allocated to one of four treatments in a randomised block design. The diet treatments were: T0 (control diets): B. ruziziensis (100%), T1 (85% B. ruziziensis + 15% Indigofera sp.), T2 (70% B. ruziziensis + 30% Indigofera sp.) T3 (55% B. ruziziensis + 45% Indigofera sp.) all on DM basis. Feed (DM) was offeredÂ daily at 3.5% BW. The content of CP in Indigofera sp is relatively high (258 g/kg DM), while the NDF (350.7 g/kg DM) and ADF (232.2 g/ kg DM) concentrations were low. The content of secondary compounds such as total phenol (8.9 g/kg DM), total tannin (0.8 g/kg DM) and condensed tannin (0,5 g/kg DM) were considerably low. The inclusion of Indigofera sp foliage in diets increased (P < 0.05) the DM, OM, CP, NDF and ADF digestibilities. The digestibility of DM (601,0 g/kg DM), OM (625 g/kg DM) and CP (699.0 g/kg DM) were highest in the T3 diets. DM intakes were greatest in the T2 and T3 diets (P < 0.05). Total gain increased 39, 78 and 85% in T1, T2 and T3 respectively, compared to that in the control diet. Daily gains were highest in the T3 (52.4 g) and T2 (50.5 g) diets, but feed efficiency was highest (P < 0.05) in the T3 diets (0,12). Feed efficiency were not different (P > 0.05) among the T0,T1 and T2 diets and ranged from 0.08 to 0.09. It is concluded that the foliage of Indigofera sp could be used as feed supplement to supply proteins with low tannin contents. In a grass-based diets Indigofera sp colud be used at the level of 30 to 45% (DM) for growing kids. Key Words: Indigofera, Inclusion Level, Feed Intake, Digestibility, ADG, Goats